In-season mineral nutrient management of citrus by early (spring/summer) season sampling of leaves, fruitlets, and flowers - Broeksma, Cornelis Reitz (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.